Saliva as a reliable diagnostic tool during the coronavirus disease times: A focused review - Sarita Shaukari; Souren Bellam; K Raghu Nandan; Revathi Peddu (Wolters Kluwer Medknow Publications, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), also currently known as CoV disease 2019 (COVID-19), has created a global health upheaval. The saliva of an infected person serves as a source for the transmission of CoV. The angiotensin-converting enzyme-2 receptors serve as the host receptor cells for CoV which is expressed in high numbers in salivary glands, oral mucosa, and gingiva. The salivary gland is a potential reservoir for COVID-19 even in asymptomatic but infected carriers. This knowledge could be used to employ salivary sampling as a noninvasive diagnostic method. IgA, IgM antibodies detected in self-collected saliva show more stability than RNA and may aid in the identification of asymptomatic patients. Saliva shows high sensitivity and specificity in the diagnosis of COVID-19 with >90% concordance reported between the saliva and nasopharyngeal swabs. Standardization with respect to sample collection, storage, and transport media can help in validation of diagnostic application of salivary-based testing.